Viral determinants of simian immunodeficiency virus (SIV) virulence in rhesus macaques assessed by using attenuated and pathogenic molecular clones of SIVmac. - Marthas, M L (1993)
To identify viral determinants of simian immunodeficiency virus (SIV) virulence, two pairs of reciprocal recombinants constructed from a pathogenic (SIVmac239) and a nonpathogenic (SIVmac1A11) molecular clone of SIV were tested in rhesus macaques. A large 6.2-kb fragment containing gag, pol, env, and the regulatory genes from each of the cloned (parental) viruses was exchanged to produce one pair of recombinant viruses (designated SIVmac1A11/239gag-env/1A11 and SIVmac239/1A11gag-env/239 to indicate the genetic origins of the 5'/internal/3' regions, respectively, of the virus). A smaller 1.4-kb fragment containing the external env domain of each of the parental viruses was exchanged to create the second pair (SIVmac1A11/239env/1A11 and SIVmac239/1A11env/239) of recombinant viruses. Each of the two parental and four recombinant viruses was inoculated intravenously into four rhesus macaques, and all 24 animals were viremic by 4 weeks postinoculation (p.i.). Virus could not be isolated from peripheral blood mononuclear cells (PBMC) of any animals infected with SIVmac1A11 after 6 weeks p.i. but was consistently isolated from all macaques inoculated with SIVmac239 for 92 weeks p.i. Virus isolation was variable from animals infected with recombinant viruses; SIVmac1A11/239gag-env/1A11 and SIVmac239/1A11env/239 were isolated most frequently. Animals inoculated with SIVmac239 had 10 to 100 times more virus-infected PBMC than those infected with recombinant viruses. Three animals infected with SIVmac239 died with simian AIDS (SAIDS) during the 2-year observation period after inoculation, and the fourth SIVmac239-infected animal had clinical signs of SAIDS. Two animals infected with recombinant viruses died with SAIDS; one was infected with SIVmac239/1A11gag-env/239, and the other was infected with SIVmac1A11/239gag-env/1A11. The remaining 18 macaques remained healthy by 2 years p.i., and 13 were aviremic. One year after inoculation, peripheral lymph nodes of some of these healthy, aviremic animals harbored infected cells. All animals seroconverted within the first few weeks of infection, and the magnitude of antibody response to SIV was proportional to the levels and duration of viremia. Virus-suppressive PBMC were detected within 2 to 4 weeks p.i. in all animals but tended to decline as viremia disappeared. There was no association of levels of cell-mediated virus-suppressive activity and either virus load or disease progression. Taken together, these results indicate that differences in more than one region of the viral genome are responsible for the lack of virulence of SIVmac1A11.